Patrones radiológicos pulmonares y recuento de linfocitos cd4+ en pacientes VIH positivos coinfectados con tuberculosis pulmonar en HNGAI diagnosticados durante los años 1994-2011 - Vega Villanueva, Karen Isabel (2014)
Background: In pulmonary tuberculosis (PTB) there are certain radiographic patterns as the cavitation, which has been considered “pathognomonic” of this disease. However, this is controversial in HIV positive patients coinfected with PTB because several studies found that there are patterns associated with CD4+ T lymphocyte count greater or slower than 200 cells/mm3 . Objectives: To determine the association between pulmonary radiographic patterns and CD4+T lymphocyte count in HIV patients coinfected with PTB. Methods: Cross- sectional study conducted at the Hospital Nacional Guillermo Almenara Irigoyen (HNGAI) of Lima, Perú, from 1994 to 2011. We worked with the online database provided by the Department of Infectious Diseases in which only 241 patients were eligible. We excluded 112 patients who did not meet the inclusion criteria established. The radiological patterns were determined from the radiology report of the medical record database, diagnosis of HIV was determined by ELISA and Western Blot test and the CD4+ count by flow cytometry. The bivariate analysis was performed using Fisher’s exact test and we considered a p <0.05 as significant. Results: The sample consisted of 129 patients, of which 77.5% were men. There was a median age of 37 years for the age of diagnosis of PTB (IQR= 30.5- 44) and the median CD4+ T lymphocyte count was 59 cells/mm3 (IQR= 22- 206). Patients with CD4+ T lymphocyte count <200 cells/mm3 represented 73.6% (n= 95). Interstitial pattern was the most frequent (25.6%) pattern of the sample, followed by the normal pattern (23.7%). Among the main findings, the pattern that had a higher prevalence of patients with CD4+ counts ≥ 200 cells/mm3 was the normal patterns with 35.14%. While the pattern that provided more patients with CD4 + counts <200 cells/mm3 was the pleural pattern with 83.33% within this group. We found no significant p value in the association between pulmonary radiographic patterns and the level of CD4+ T lymphocytes count. Conclusions: No association was found between radiological patterns and CD4+ lymphocyte count. It is possible to find any pattern in this group of patients. We do not recommend trying to determine the CD4+ count from the chest radiograph in HIV patients coinfected with PTB. It would be important to conduct further multicenter studies